Patterns of failure and prognosis in nasopharyngeal carcinoma according to Epstein-Barr virus DNA status - Lin-Feng Guo; Guan-Zhong Lu; Zhen-Zhen Lu; Yi-Feng Yu; San-Gang Wu (Infectious Agents and Cancer)
Abstract Purpose To investigate the patterns of failure and prognosis in recurrent or metastatic nasopharyngeal carcinoma (rmNPC) according to Epstein-Barr virus-DNA (EBV-DNA) status. Methods We included NPC patients who were diagnosed with locoregional recurrence (LRR) and/(or) distant metastasis (DM) between January 2017 and June 2024. Receiver operating characteristic analysis, Chi-square test, Wilcoxon rank sum test, Kaplan-Meier method, and Multivariate Cox regression analyses were used for statistical analysis. Results This study involved 108 patients, including 105 (97.2%) who had EBV-DNA detectable at the initial diagnosis of NPC. Regarding progression patterns, 34 patients (31.5%) experienced only LRR, while 60 patients (55.6%) had only DM. LRR followed by DM was observed in 5 (4.6%) patients, DM followed by LRR occurred in 2 (1.8%) patients, and both LRR and DM were presented simultaneously in 7 (6.5%) patients. EBV-DNA positivity rates significantly differed between LRR and DM patients, at 76.9% and 97.1% respectively (P = 0.003). A significant difference was also observed in EBV-DNA levels, with a median level of 413 copies/mL for LRR and 6,550 copies/mL for DM (P < 0.001). While the EBV-DNA positivity rate did not differ significantly between oligometastatic disease and polymetastatic disease (P = 0.493), the levels were significantly elevated in the polymetastatic disease group than the oligometastatic disease group (P < 0.001). Multivariate analysis showed that liver metastasis (P = 0.012) and EBV-DNA levels ≥ 3,525 copies/mL at progression (P = 0.009) independently correlated with poorer overall survival. Conclusions Our study provides substantial evidence linking higher EBV-DNA levels with disease failure patterns and identifies liver metastasis and EBV-DNA levels at disease progression as independent prognostic factors for poorer overall survival in rmNPC patients.